Tra Vinh University first year English majors’ attitudes toward listening comprehension exercises in intermediate english speaking & listening classes - Nguyen Huu Van Mi (Trường Đại học Trà Vinh, 2018)
The study attempts to explore a broad view and in-depth knowledge about the understanding of how Tra Vinh university first year English majors’ attitudes toward listening comprehension exercises in terms of behavioral and cognitive aspects.